INTEGRASI METODE DISKUSI MENGGUNAKAN TELEGRAM DISCUSSION GROUP DALAM PEMBELAJARAN PAI DI SMA - Syafruddin Syafruddin (Al'Adalah, 2019)
This study examines the optimization of the Islamic education learning by the virtual discussion groups through the integration of Telegram application in SMA Negeri 1 Meulaboh class XII IPA 5. The results showed that the learning and teaching were optimized and integrated between the various components of learning such as approaches, strategies, models, methods, and use of technology tools. The results of the optimization process include: 1) a lesson plan has been compiled with a blended learning approach, 2) group worksheets are available, 3) group rules have been arranged, 3) technical guidance for online discussions, 6) guest teachers, and, 5) provide reward. By integrating and harmonizing the various components of learning, it is possible to obtain maximum process and results.